The impact of waiting intervals on survival outcomes of patients with endometrial cancer: A systematic review of the literature. (March 2020) - Pergialiotis, Vasilios; Haidopoulos, Dimitrios; Tzortzis, Andrianos Serafeim; Antonopoulos, Ioannis; Thomakos, Nikolaos; Rodolakis, Alexandros
Abstract: The purpose of the present systematic review is to summarize the available evidence concerning the impact of investigated intervals of treatment (diagnosis to surgery and surgical treatment to adjuvant therapy) on survival outcomes of endometrial cancer patients. We searched Medline, Scopus, Clinicaltrials.gov, EMBASE, and Google Scholar databases from inception until July 31st 2019. All observational studies were considered eligible for inclusion. Investigated outcomes were retrieved and analyzed as well as factors that influenced the extent of wait intervals. Overall, 12 articles were included that investigated the influence of wait intervals on survival outcomes of 773, 185 patients. We observed that the proposed cut-off values for interval periods, the reported survival outcomes as well as the tumor characteristics of included patients varied significantly among the studies that were included. Given these differences, meta-analysis of survival outcomes was not possible. The most common cut-off for the time to surgery interval was 6 weeks and for the time to adjuvant treatment 9 weeks. The percentage of patients that was treated within this limit ranged between 24 and 74 %. Given this information we believe that the optimal interval between diagnosis and surgical treatment of endometrial cancer patients should not exceed eight weeks (keeping in mind that surgery within the first two weeks may be a negative prognostic factor), whereas between surgery and adjuvant therapy should be limited to a maximum of nine weeks. Future studies should evaluate factors that seem to influence the extent of waiting intervals to help determine the limitations of healthcare systems.